Diplomacy Conceptualization For The Security State On Mineral Resources In Indonesia - Ahmad Redi; Tina Amelia (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Diplomacy is considered for the security state on mineral resources in Indonesia since Indonesia is a law country and has many mining sector possibilities which need to be secured, and created in response to reduce negative impact on mineral illegal mining activities which cause many negative results for Indonesia. Therefore, the Indonesia government needs an alternative effort which lines with the principles concluded by this research. By literatrue reviews employed for the investigation on some international practices published by reputable-indexed journals with the same issue, this research performs an information for the armed forces and the leadership of the Ministry of Law and Human Rights. In the absence of a generally accepted definition of "mineral mining activity diplomacy," the state (in this case, Indonesia) attempts to tailor its content to the requirements of the mineral resource security strategy. The study results that diplomacy involving natural resource mining has broad applicability to Indonesia since it encompasses state security policy creation and execution, as well as the establishment of permanent, cooperative international ties in the defense sector. The first step in realizing the concept's potential as a significant instrument is to conceptualize the mineral resource mining activity diplomacy for the security state in Indonesia from illegal mining activities.